Too little, too late: Socioeconomic disparities in the experience of women living with diabetes. (May 2014) - Nicklett, Emily Joy; Damiano, Sara Kuzminski
The purpose of this article is to examine whether or not subjective social status contributes to diabetes diagnosis and disease discovery experiences. Eighteen diabetic women participated in semi-structured interviews. Interview transcripts were reviewed and coded using interpretative phenomenological analysis. Several general themes emerged from the data analysis: subjective social status shaped different experiences through (a) situations of diabetes discovery (including the circumstances and stage of diabetes at the time of diagnosis), (b) the degree to which participants considered diabetes to be manageable, (c) the extent of diabetes-related knowledge and experience before diagnosis, and (d) opportunities to gain knowledge shortly thereafter. Due to these constraints, lower subjective social status individuals had particularly adverse disease discovery experiences. The findings are consistent with the theory of constrained choices. Implications for practitioners and for future research are discussed.